Uniformização e representação computacional dos dermátomos humanos - Silva, Naila Luisa Saiki da (2011)
Dermatome is an area of skin innervated by posterior (primary) and anterior (primary) rami or roots [posterior (primary) rami of spinal nerves supply the back; the anterior (primary) rami of spinal nerves supply the plexuses] of a metameric sensory spinal segmentation. The dermatomes are named according to their anatomical distribution or segmental innervation. Dermatome maps of the body are critical in topographical cutaneous studies in order to make an accurate diagnosis of radicular, truncal, fascicular, medullar, or neural terminal lesions. However, human dermatomes segmental cutaneous innervation is discordant, presenting inaccurate boundaries and does not present uniform projections of Surface Anatomy. In addition, the reference does not represent all dermatomes, usually explained under the restricted visualization field. Computer graphics has provided significant contributions in the analysis of anatomical knowledge and may be useful to unify and represent the human dermatomes three-dimensionally. This study aims to uniformize and to promote the three-dimensional representation of human dermatomes through a computer program. The survey and evaluation was composed of 342 Textbooks on Health and Applied Health Sciences (Anatomy, Physiology, Orthopedics, Neurology, Internal Medicine, Dermatology, Physical Therapy, Occupational Therapy, Nursing, and Dentistry) was carried out at the Sao Jose do Rio Preto medical School library. Of the 342 textbooks, 75 were used in the study (based on the degree of anatomical proportion and reliability of image or content). A scanning device was used to digitalize the images related to the cutaneous innervation in several visualization fields. These images were analyzed using a Multifunction Printer Lexmark® and the Adobe Photoshop Software® 7.0. The total body surface area, the surface area of each dermatome, measures of central tendency and dispersion under different visualizations were obtained. At first, 202 images were digitalized. Following critical analysis (excluding overlapping images, oblique projection, and unintelligible mapping), radiographic projections were devised to obtain a direct visualization of the dermatomes. It was obtained 69 anterior projections, 63 posterior projections, 18 lateral projections, five medial projections, and three in the gynecological position, with subsequent standardization of representation of human dermatomes from several angles of visualization, including animation effect in AVI (Audio Video Interleave). A careful selection of the images followed by a systematization and the working up by computer programs allow the uniformness and representation of human dermatomes in a groundbreaking way (exposure of areas not visible to the Position of Anatomical Description and the preparation of teaching videos with standard dimensional visualizations). This allows additional applicability of both Teaching and Learning in Clinical Anatomy, Medical Imaging, or Surgery.